Innovation in Russian District Heating: Opportunities, Barriers, Mechanisms - Andrey Kovalev; Liliana Proskuryakova (Foresight and STI Governance)
Contrary to more advanced countries, Russia’s district heating hardly embraces radical innovations. Moving forward with breakthrough solutions, even if they have proven their effectiveness at leading European companies and are supported by federal and regional authorities, encounters significant obstacles. These obstacles include inflexible corporate management, including when interacting with customers, and inexperience in creating internal corporate startups and managing risks in the early stages of R&D.